1990
DOI: 10.1128/aac.34.6.1118
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerance, and pharmacokinetic evaluation of cefepime after administration of single intravenous doses

Abstract: In this double-blind, single-dose phase I study, the safety and tolerance of cefepime were assessed in 24 healthy male subjects, with ceftazidime as the control drug. Four subjects in each of the six dose groups (62.5, 125, 250, 500, 1,000, or 2,000 mg as a 30-min itravenous infusion) received each antibiotic, according to*a crossover design, with a 2-day washout period between treatments. Blood and urine samples were obtained to characterize the pharmacokinetics of cefepime. Plasma and urine samples were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 17 publications
5
50
2
Order By: Relevance
“…The current study showed that the pharmacokinetic parameters for the test formulation, Cefamax, and the reference formulation, Maxipime, are not significantly different, except for CL The pharmacokinetic parameters for Cefamax obtained from the current study were higher than the results from a previous study [2,5,6], which may be the result of the lower body weight of the volunteers in this study. Thus, the drug concentrations of Cefamax were higher than recommended levels for treatment of the infections for which this substance is approved.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The current study showed that the pharmacokinetic parameters for the test formulation, Cefamax, and the reference formulation, Maxipime, are not significantly different, except for CL The pharmacokinetic parameters for Cefamax obtained from the current study were higher than the results from a previous study [2,5,6], which may be the result of the lower body weight of the volunteers in this study. Thus, the drug concentrations of Cefamax were higher than recommended levels for treatment of the infections for which this substance is approved.…”
Section: Discussioncontrasting
confidence: 56%
“…All subjects had good tolerance and no serious adverse events were observed. Conclusion: Cefamax 1 g intramuscular formulation is bioequivalent to Maxipime 1 g intramuscular formulation based on 90% CIs for C max, AUC [0][1][2][3][4][5][6][7][8][9][10][11][12] , and AUC 0-∞ within 80%-125%. …”
mentioning
confidence: 99%
“…In addition, cefepime appears to have a low affinity for chromosomally derived P-lactamases (23). Clinical experience indicates that cefepime is safe and well tolerated when single or multiple (every 8 or 12 h) doses of 250 to 2,000 mg are given by the intravenous (4,5) or intramuscular (9) routes of administration. The pharmacokinetics of this cephalosporin are linear (4,5,9).…”
mentioning
confidence: 99%
“…Clinical experience indicates that cefepime is safe and well tolerated when single or multiple (every 8 or 12 h) doses of 250 to 2,000 mg are given by the intravenous (4,5) or intramuscular (9) routes of administration. The pharmacokinetics of this cephalosporin are linear (4,5,9). Over 80% of the administered dose of cefepime is recovered in urine in an unchanged form (4,5,(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation